Comprehensive Therapy for Infant Vascular Tumor Associated With Kasabach–Merritt Phenomenon—Single-Center Primary Experience - Sun, Xiaoting; Xu, Miao; Lv, Kaiyang; Ma, Xiaorong; Wu, Liming; Ouyang, Tianxiang (Frontiers in Pediatrics, 2022)
Objective To introduce our single-center experience of infant vascular tumor associated with Kasabach–Merritt phenomenon (KMP) which received combined medicine treatment with intralesional laser photocoagulation (ILP) and sclerotherapy. Methods A retrospective study was conducted using medical records of all children with a diagnosis of kaposiform hemangioendothelioma (KHE) or tufted angioma (TA) associated with KMP treated with medicine, intralesional laser photocoagulation (ILP), and sclerotherapy between February 2017 and November 2020. Clinical features, response to comprehensive therapy, and outcomes were recorded. Results A total of 23 patients including nine females (39%) and 14 males (61%) were identified. The mean age was 6.9 months (age range, 11 days−2 years) at the time of treatment. Nine children (39%) demonstrated sensitivity to single corticosteroid therapy; 14 children (61%) received combined therapy with intravenous Vincristine (VCR) and corticosteroid therapy. All children had at least two ILP and sclerotherapy performed, with a mean of 3.5 procedures (range: 2–6). Of these 14 children, only one experienced a relapse of thrombocytopenia and the remaining 13 children had no clinical symptoms recurred. Conclusion The combined therapy modalities could induce a more rapid tumor response and resolution of KMP and decrease the rebound rates. This research presents a novel and safe multi-modality treatment for infant vascular tumors associated with KMP.